PROFIL SELF-REGULATED LEARNING MAHASISWA PROGRAM STUDI BIMBINGAN DAN KONSELING FIP UNM - Akbar_Naim_Fadhllillah; Abdullah Pandang; Farida Aryani (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2024)
Self-regulated learning (SRL) is the ability of students to control cognition, emotions, and behaviors in order to achieve their learning goals independently. This research aims to identify the SRL profile of students of the FIP UNM Guidance and Counseling Study Program Class of 2022. The method used was a descriptive survey with a questionnaire as an instrument for collecting data from 55 students. The survey results showed that 73% of students were in the high SRL category, while 27% were in the low SRL category, and none were in the very high or very low category. Students with low SRL tend to experience problems such as lack of motivation, poor time management, and weak critical thinking skills. This study shows the importance of interventions to improve students' SRL abilities, especially in the aspects of motivation, learning planning, and metacognitive skills, so that they can be more optimal in achieving academic goals.Self-regulated learning (SRL) adalah kemampuan mahasiswa untuk mengendalikan kognisi, emosi, dan perilaku guna mencapai tujuan belajarnya secara mandiri. Penelitian ini bertujuan mengidentifikasi profil SRL mahasiswa Program Studi Bimbingan dan Konseling FIP UNM Angkatan 2022. Metode yang digunakan adalah survei deskriptif dengan kuesioner sebagai instrumen pengumpulan data dari 55 mahasiswa. Hasil survei menunjukkan bahwa 73% mahasiswa berada dalam kategori SRL tinggi, sementara 27% berada dalam kategori SRL rendah, dan tidak ada yang berada dalam kategori sangat tinggi atau sangat rendah. Mahasiswa dengan SRL rendah cenderung mengalami masalah seperti kurangnya motivasi, manajemen waktu yang buruk, dan lemahnya keterampilan berpikir kritis. Penelitian ini menunjukkan pentingnya intervensi untuk meningkatkan kemampuan SRL mahasiswa, terutama pada aspek motivasi, perencanaan belajar, dan keterampilan metakognitif, agar mereka dapat lebih optimal dalam mencapai tujuan akademik.